Is the willingness to take financial risk a sex-linked trait? Evidence from national surveys of household finance - Nataliya Barasinska; Dorothea Schäfer (Deutsche Bundesbank, 2013)
We investigate whether the willingness to take investment risk is a sex-linked trait and link the results to the country's gender equality regime. Our empirical analysis involves household data on financial asset holdings as well as on self-reported risk tolerance for Austria, Italy, the Netherlands and Spain. Of those countries, Italy is by far the country with the greatest degree of gender inequality according to the 2009 Global Gender Gap Report. Two stages of building a portfolio of financial assets are analyzed. For the first-stage decision of whether to invest in risky assets in the first place, gender is found to have no effect in Austria, the Netherlands and Spain but does have an impact in Italy. However, even for Italy, it seems to be irrelevant in the second-stage decision about the share of wealth invested in the risky assets. We infer from these findings that, for countries with a high degree of gender equality, it is inappropriate to base financial advice primarily on gender.
Keywords: G11; J16; 330; gender; risk aversion; financial behavior